THE RELATIONSHIP BETWEEN MATHEMATICAL DISPOSITION AND SELF-REGULATED LEARNING TO MATHEMATICAL PROBLEM-SOLVING ABILITY - Nida Firdaus; Rika Sukmawati; Warsito Warsito (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Problem-solving skills are one of the important competencies that students need to have, but they are still influenced by various factors such as mathematical disposition and self-regulated learning. This study aims to determine the relationship between mathematical disposition and self-regulated learning to mathematical problem-solving ability. The research uses a quantitative approach with a correlational method. The research sample amounted to 71 grade VII students who were determined using the Slovin Formula and selected using the Proportionate Stratified Random Sampling technique. Data collection was carried out through a mathematical disposition questionnaire, a self-regulated learning questionnaire and a mathematical problem-solving ability test. Data analysis uses Pearson correlation, multiple correlation, and multiple linear regression analysis. The results showed that mathematical disposition had a positive relationship with a low relationship rate with mathematical problem-solving ability with a correlation value of 0.361. Self-regulated learning has a positive relationship with a low relationship level with mathematical problem-solving ability with a correlation value of 0.311. Together, mathematical disposition and self-regulated learning had a positive relationship with a low relationship rate on mathematical problem-solving ability with a correlation value of 0.371 and a contribution of 13.7%. The results of this study show that mathematical problem-solving ability is influenced by various factors other than mathematical disposition and self-regulated learning. Kemampuan pemecahan masalah merupakan salah satu kompetensi penting yang perlu dimiliki siswa, namun masih dipengaruhi oleh berbagai faktor seperti disposisi matematis dan kemandirian belajar. Penelitian ini bertujuan untuk mengetahui hubungan disposisi matematis dan kemandirian belajar terhadap kemampuan pemecahan masalah matematis. Penelitian menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel penelitian berjumlah 71 siswa kelas VII yang ditentukan menggunakan Rumus Slovin dan dipilih memalui teknik Proporsionate Stratified Random Sampling. Pengambilan data dilakukan melalui angket disposisi matematis, angket kemandirian belajar dan tes kemampuan pemecahan masalah matematis. Analisis data menggunakan korelasi Pearson, korelasi berganda, dan analisis regresi linier berganda. Hasil penelitian menunjukkan dispossi matematis memiliki hubungan positif dengan tingkat hubungan rendah terhadap kemampuan pemecahan masalah matematis dengan nilai korelasi sebesar 0,361. Kemandirian belajar memiliki hubungan dengan positif dengan tingkat hubungan rendah terhadap kemampuan pemechan masalah matematis dengan nilai korelasi sebesar 0,311. Secara bersama-sama, disposisi matematis dan kemandirian belajar memiliki hubungan positif dengan tingkat hubungan rendah terhadap kemampuan pemecahan masalah matematis dengan nilai korelasi sebesar 0,371 dan kontribusi sebesar 13.7%. hasil penelitian ini menunjukkan kemampuan pemecahan masalah matematis dipengaruhi berbagai faktor selain disposisi matematis dan kemandirian belajar.